Characterization of the waste from the electronic industry - Raj Kumar, Masilamoney (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Many chemicals and raw materials are used in the manufacture of printed circuit boards. Most of them contain hazardous substances such as toxic substances like heavy metals, organic compounds, alkalis, acids and others which may effect the environment if they are allowed to be discharged in the waste without being removed. Therefore an understanding of the properties and character of waste is essential for environment quality control through the selection of suitable ways to handle waste and also to in the process gain economical by evaluating the potential for recovery e.g. for metals. The data which are collected to evaluate the waste water are essential to achieve environmental standards like achieve ISO 14000. The treated wastewater effluent and sludge generated from this industry were characterized. The results compared with the effluent discharge limits prescribed in the Environmental Quality (Sewage and Industrial Effluents) Regulation 1979 by the Department of Environment (DOE). The parameters tested were physical properties (pH, temperature, conductivity, dissolved oxygen, turbidity, and suspended solids) inorganic nonmetallic constituents (ammoniacal nitrogen, chloride, phosphate, sulphate, cyanide, and sulfide) organic constituents (BODs, COD, oil and grease) and heavy metals (lead, cadmium, copper, manganese, zinc, iron, gold, mercury and calcium). All of these parameters accept copper complied with the standard B discharge limit as stated. For material recovery the copper was found to merit further feasibility. Key words: electronic industry, wastewater effluents, sludge ..